Third generation biofuels: A nutritional perspective in enhancing microbial lipid production - Leong, W.-H. (Elsevier Ltd, 2018)
The third generation biofuels derived from oleaginous microorganisms have gained traction recently as the potential feedstock in generating fuel for energy production, reducing the direct dependence on fossil fuels. However, commercialization of microbial technology for biofuel production remains intricate and questionable due to many factors concerning the life cycle assessment and techno-economic feasibility of microorganisms-based biofuels. This review initially focuses on the nutritional aspects in enhancing the biomass and lipid yields from various microorganism feedstock, serving as impetuses for the production of third generation biofuels. Nutrient optimizations in terms of nutrient starvation, supplementation and balancing technique are discussed in relation to their respective effects on the microbial biomass and lipid productions. More importantly, the economic perspectives of oleaginous microorganism cultivations are also reviewed and strategized using alternative and non-conventional nutrient sources for possible technology scale-ups and commercialization. Â© 2018 Elsevier Ltd